Methane Emissions and Milk Fatty Acid Profiles in Dairy Cows Fed Linseed, Measured at the Group Level in a Naturally Ventilated Housing and Individually in Respiration Chambers - Jernej Poteko; Sabine Schrade; Kerstin Zeyer; Joachim Mohn; Michael Zaehner; Johanna O. Zeitz; Michael Kreuzer; Angela Schwarm (Animals, 2020)
The present study evaluated the effects of linseed supplementation on CH4 emission and milk fatty acid composition in dairy cows measured at the group level in an experimental dairy loose housing using a tracer gas technique and individually in tied stalls and respiration chambers. Cows (2 × 20) were maintained in two separate sections under loose-housing conditions and received a diet supplemented with extruded linseed (L) lipids (29 g·kg−1 dry matter) or a control (C) diet containing corn flour. Subsequently, 2 × 6 cows per dietary group were investigated in a tied-housing system and respiration chambers. Substantially higher proportions of favorable milk fatty acids were recovered in L cows when compared with C cows at the group level, making the analysis of bulk milk a suitable control instrument for retailers. Linseed supplementation resulted in a slightly lower diurnal course of CH4 emission intensity than the control at the group and individual levels. However, we found no more than a trend for a CH4 mitigating effect, unlike in other studies supplementing similar linseed lipid levels. Feed supplements in concentrations that lead to a significant reduction in CH4 emissions must show whether the reduction potential determined at the group and individual levels is comparable.